Peripheral blood lymphocyte subsets predict the efficacy of TACE with or without PD-1 inhibitors in patients with hepatocellular carcinoma: a prospective clinical study - Wang, Hongyu; Huang, Huijie; Liu, Ting; Chen, Yaoming; Li, Jinwei; He, Min; Peng, Jianxin; Liang, Enyu; Li, Jiaping; Liu, Wendao (Frontiers in Immunology, 2024)
Background: Although peripheral blood lymphocyte subsets, particularly PD-1+ T cells, are promising prognostic indicators for patients with cancer. However, their clinical significance remains unclear.We prospectively enrolled 157 patients with hepatocellular carcinoma (HCC) treated with transcatheter arterial chemoembolization combined with or without PD-1 inhibitors. Twenty peripheral lymphocyte subsets and cytokines were analyzed. We analyzed the differences in PD-1+ T cells between patients treated with and without PD-1 inhibitors and their associations with tumor response, survival prognosis, and clinical features.We found that the baseline CD8+PD-1+ and CD4+PD-1+ T-cell frequencies in patients who had received PD-1 inhibitors were lower than those in patients who had not received PD-1 inhibitors (p < 0.001). In the former patients, there were no differences in PD-1+ T-cell frequencies between the responder and non-responder subgroups (p > 0.05), whereas in the latter patients, the levels of CD8+PD-1+ T cells, CD4+PD-1+ T cells, and CD8+PD-1+/CD4+PD-1+ ratio did not predict tumor response, progression-free survival (PFS), or overall survival (OS) (p>0.05). Furthermore, in multivariate analysis of patients treated with or without PD-1 inhibitors revealed that the levels of CD8+CD38+ T cells (OR = 2.806, p = 0.006) were associated with tumor response, whereas those of CD8+CD28+ T cells (p = 0.038, p = 0.027) and natural killer (NK) cells (p = 0.01, p = 0.001) were associated with PFS and OS. Although, these independent prognostic factors were associated with progressive tumor characteristics (p<0.05), with the exception of CD8+CD28+ T cells, changes in these factors before and after treatment were unassociated with tumor response (p > 0.05).Circulating CD8+CD38+ T cells, CD8+CD28+ T cells, and NK cells were identified as potential prognostic factors for tumor response and survival in patients with HCC. Contrastingly, although PD-1 inhibitors can effectively block the T cell PD-1 receptor, the baseline PD-1+ T-cell frequencies and changes in the frequency of these cells have limited prognostic value.